Cyprinus Carpio: biological features, ecology and diseases and control Measures - Rahman, Mohammad Mustafizur (NOVA Science Publishers, 2018)
As a freshwater fish, common carp (Cyprinus carpio) is perhaps one of the most well known species and attracts global attention being one of the most widespread aquaculture species and a key target of research globally. In Asia and Europe, it is considered a key food fish that contributes approximately 4% of the total global aquaculture production and 9% of the global freshwater aquaculture production. In many European countries, it is the most cultured fish species and is considered the backbone of their aquaculture industry. In North America, New Zealand and Australia, it is considered as an invasive and noxious aquatic species that has profound negative impacts on water quality, aquatic plants, native fish populations and more widely entire aquatic ecosystems. Considering its local importance, most of the research conducted in Europe and Asia has primarily focused on the aquaculture and ecology of carp in ponds particularly their effects on water quality, aquatic plants and native fish populations, while most of the research in other parts of the world is focused on management of carp in natural habitats, particularly how to mitigate various detrimental impacts of common carp on local fish species. Due to worldwide dispersion, common carp display immense spatial differences in their growth, production, food habit, spawning, maturation and fecundity. However, there has been a limited focus on on carp research at a global scale. This book seeks to review the biology and ecology of common carp with a global focus. The common carp is primarily a benthic dweller and prefers to feed on benthic organisms, zooplankton and a wide variety of decayed organic material. Due to their benthic food preference, common carp is susceptible to various viral, bacterial, fungal and parasitic diseases at various stages of their life. The information about ethology provides essential information helping aquaculturists to prevent the disease. Information regarding various diseases of common carp is very scattered. A single document, which describes various diseases of common carp is almost lacking. Therefore, in addition to biology and ecology, this book provides information both traditional and novel methodologies of identifying various diseases of common carp, together with the methods and management particularly preventative and control measures. Seven chapters provide up to date information about biology, ecology, and various diseases and control measures of common carp. We hope that this book will be of interest to aquaculturists, students and researchers.